Protocols for detection and prevention of RhD alloimmunisation during pregnancy - Velkova E; Ismaili A; Useni S; Dejanova-Ilijevska V; Mitevska L (SHMSHM / AAMD, 2015)
Mother’s alloimmunisation during pregnancy, also known as isoimmunisation, is defined as a presence of irregular Red Blood Cells (RBC’s) alloantibodies in blood of pregnant woman that can lead to Hemolytic Disease of the Fetus and Newborn (HDFN) or in severe cases to fetal demise. Aim: to evaluate the RhD alloimmunisation during pregnancy among women in R. Macedonia and to propose protocols that will improve healthcare and women safety during pregnancy. Material and method: for 22.009 pregnant women in the period of 2004-2014, were done immunohematology analyses: ABO blood group and Rh type, screening of RBC’s alloantibodies, Indirect Antiglobulin Test (IAT) with 5 panels of RBC’s antigens, enzyme test (two panels of RBC’s antigens), identification of RBC’s antibodies (Coombs and enzyme panels), quantification of antibodies and blood group phenotypisation. Results: total of 3.838 (17.42%) pregnant women were RhD negative. RBC’s alloantibodies were detected among 205 women, out of which 169 had sensitization toward RhD antigen and 36 pregnant women had multiple antibodies. The prevalence of allosensibilisation in R. Macedonia is 4.74%; 112 (54.62%) RhD sensitized pregnant women didn’t receive antenatal prophylaxis. Symptoms of HBFN didn’t show 50.93% of newborns, mild or strong intensity had 36.11% and 12.5% had fetal demise. Conclusion: The most often reason for RhD sensitization of pregnant women in R. Macedonia is the lack or inappropriate antenatal prophylaxis. It is expected that the wide use of a proposed new protocols will decrease the percentage of women’s RhD sensitization and the morbidity and mortality of newborns with HDFN.
Keywords: Hemolytic Disease of the Fetus and Newborn (HDFN); Feto - Maternal Hemorragi (FMH); antenatal and postnatal RhD prophylaxis; alloimmunisation